Identifying people at risk for influenza with low vaccine uptake based on deprivation status: a systematic review. (28th September 2019) - Vukovic, Vladimir; Lillini, Roberto; Lupi, Silvia; Fortunato, Francesca; Cicconi, Michela; Matteo, Giulio; Arata, Lucia; Amicizia, Daniela; Boccalini, Sara; Bechini, Angela; Prato, Rosa; Stefanati, Armando; et al.
Abstract: Background: Influenza vaccination is an important public health intervention for controlling disease burden, but coverage rates are still low also in risk groups. In order to identify non-vaccinating subgroups, deprivation and socio-economic indices, i.e. measures used to synthetically describe people's socio-economic status while taking into account several dimensions, may be used. We aimed to synthetize evidence from studies investigating association between deprivation/socio-economic indices and influenza vaccination coverage in population at risk—persons ≥65 years of age, individuals with comorbidities, pregnant women and health-care workers. Methods: We searched PubMed, ISI WoS, CINAHL and Scopus to identify observational studies published up to October 10th 2017 in English or Italian. Studies reporting quantitative estimates of the association between deprivation/socio-economic indices and influenza vaccination coverage in populations at risk were included. Results: A total of 1474 articles were identified and 12 were eventually included in the final review. Studies were mostly cross-sectional, performed in European countries, from 2004 to 2017. Seven studies focussed on deprivation and five on socio-economic indices. Studies on deprivation indices and vaccination coverage showed that people from the most deprived areas had lower coverage. Regarding socio-economic condition, results were contrasting, even though it may also be concluded that people from lower groups have lower vaccination coverage. Conclusions: Our work supports the possibility to identify people likely to have lower influenza vaccination coverage based on deprivation/socio-economic indices. Efforts should be performed in order to further strengthen robustness, transferability and suitability of these indices in addressing public health problems.